Creation theology in Psalm 139 - Mare, Leonard P. (Old Testament Essays, 2010)
The first reference in the Bible to God's activities is "in the beginning, God created." This puts "Creator" at the top of the list of descriptions of who Yahweh is and what Yahweh does. This implies that Yahweh stands in relationship with the world, and not only with Israel. Israel was created to be his people as a result of him being the Creator of the world. He is therefore the God of all humanity and the ultimate source of creation. God's creative actions began "in the beginning," but it did not stop there. God's creative activities include originating, continuing and completing creation. There are an abundance of creation texts in the Old Testament. Genesis, Exodus, the legal texts of the Pentateuch, the prophets, wisdom texts and the psalms all contribute to the OT theology on creation. My purpose with this article is to analyse Psalm 139 to determine how this psalm articulates creation theology. Creation theology plays a decisive role in every aspect of the psalm. God's omniscience (vv. 1- 6), his omnipresence (vv. 7-12), his creation of humankind (vv. 13-18) and the petition for vengeance and transformation (vv. 19-24) should be understood within the framework of creation theology.
free